New insight in the biological integration of polytetrafluoroethylene from an explant used for diaphragm repair. (January 2017) - Schneider, Anne; Talon, Isabelle; Mathieu, Eric; Schaaf, Pierre; Becmeur, François; Hemmerlé, Joseph
Congenital diaphragmatic hernia is a severe disease requiring diaphragm replacement mostly with expanded polytetrafluoroethylene. Unfortunately, the recurrence rate is high due to prosthesis failure with significant morbidity for the child. To provide a better understanding of the integration and possible failure processes of the biomaterial implanted in humans, we conducted electron microscopical and mechanical assessments on a prosthesis explant from a child with congenital diaphragmatic hernia presenting a recurrence. Our findings show a major penetration of connective tissue into the expanded polytetrafluoroethylene on the rough side, whereas the smooth side presents few tissue colonization. This penetration is more important in the central area (area A) with large collagen bundles and layers, in comparison to the peripheral areas without prosthesis failure (area B), where few extracellular matrix is produced. The connective tissue penetrates the prosthesis in depth. In contrast, the peripheral areas with prosthesis failure (area C) show very few cells and extracellular matrix, with an oriented organization in comparison to areas A and B. Obviously, the forces applied on the implanted material modulate the cellular behavior of the newly developed tissues. Atomic force microscopic measurements of the biomaterials' surfaces may explain some cellular behaviors according to areas with or without failure.